Patients with low activation level report limited possibilities to participate in cancer care - Bodil Westman; Karin Bergkvist; Andreas Karlsson Rosenblad; Lena Sharp; Mia Bergenmar (Wiley, 2022)
Abstract Background Cancer care trajectories are often complex, with potent multimodality treatments and multiple interactions with health care providers. Communication and coordination are challenging and the patients' responsibilities to take on more active roles in their own care are increasing. Objective This study aimed to investigate associations between patient activation level and participation in cancer care, sociodemographic characteristics, clinical data, health‐related quality of life (HRQoL) and helpfulness of received information. Methods In this cross‐sectional population‐based study, patients completed questionnaires on patient activation, perceived participation, HRQoL, helpfulness of received information and sociodemographic characteristics. Responses to the patient activation measures (PAMs) were classified into four levels (higher levels indicating more activation). Data on age, sex and cancer diagnosis were collected from the Swedish Cancer Register. Results Data from 682 patients were analysed. On comparing patients at PAM levels 1 and 4, the latter reported significantly higher possibilities to influence care decisions (46.6% vs. 20.8%) and to ask questions regarding treatment and care (93.4% vs. 68.4%). Patients at PAM level 4 reported wanting to influence decision‐making to a higher extent, compared with patients at other PAM levels, and reported clinically significantly higher HRQoL. No significant differences were found regarding sociodemographic characteristics. Conclusion We found strong associations between perceived patient participation and activation levels, with limited possibility for participation among those with lower activation levels. Patient or Public Contribution Discussions with patient representatives have raised the importance of participation. The preliminary findings were presented and discussed in a workshop with representatives from 21 cancer patient advocacy groups.